1609e Stakeholder perspectives of return-to-work success. (24th April 2018) - Williams-Whitt, K; Cullen, K; Gross, DP; Steenstra, I; Shaw, WS; Young, A; Nieuwenhuijsen, K
Abstract : Introduction: While a large number of measures have been used to assess return-to-work (RTW) outcomes for injured workers, none are comprehensive and few have been consistently utilised, or psychometrically tested. Researchers have long recognised that there is no standard or universal RTW outcome measure, and that this is a significant problem for program and intervention comparison. Furthermore, it is unclear whether conceptions of success are different for physical and mental health conditions. The purpose of this study is to develop and test a return-to-work success scale focused on at work success, rather than preparation to return. Methods: Phase I involves collaborative generation of potential scale items and sorting the items into similar dimensions or categories using a focus group method. Phase II involves preliminary data collection and Q-sort analysis. Phase III involves initial psychometric evaluation of reliability and validity for the initial scale in workers with mental health conditions and physical work injuries. Results: The results of Phase I will be reported. Stakeholders including workers with physical and mental health conditions, employers, insurers and occupational health practitioners participate in focus groups to generate 'return-to-work' success items. Participants are asked to identify one thing that indicates that a worker with a physical health condition has successfully returned to work, and one thing that indicates a worker with a mental health condition has successfully returned to work. The items generated are collaboratively sorted and categorised through a consensus building process. Conclusion: Scale development will support improvement in RTW practice by producing a reliable set of measures that can be used to assess interventions or stakeholder programs and processes. From a theoretical perspective, the RTWSS will improve research by providing a psychometrically sound tool to more thoroughly measure RTW outcomes. It will also facilitate knowledge synthesis in systematic reviews and meta-analysis because the outcomes are directly comparable.